How do you solve the following system?: #9y = -3x - 9 , 5x + 3y = -3 #

1 Answer
Apr 7, 2018

Answer:

Substitution/Elimination/Graphing Method

Explanation:

Using the substitution method, starting with the first equation:

#9y = -3x-9#

#9y+9 = -3x#

#(9y)/-3+9/-3 = (-3x)/-3#

#x = -3y -3#

Substituting #(x=-3y-3)# into the second equation to find #y#:

#5x+3y = -3#

#5(-3y-3) + 3y=-3#

#-15y-15 + 3y=-3#

#-12y=12#

#y=-1#

Now substituting #(y=-1) # into second equation to find #x#:

#5x+3y = -3#

#5x+3(-1)=-3#

#5x-3 = -3#

#5x= 0#

#x =0#

Test #(x=0, y=-1)# in other equation to validate

#9y = -3x-9#

#9(-1) = -3(0)-9#

#-9 = -9#,